Improved induced innate immune response after cART initiation in people with HIV - Hove-Skovsgaard, Malene; Møller, Dina Leth; Hald, Annemette; Gerstoft, Jan; Lundgren, Jens; Ostrowski, Sisse Rye; Nielsen, Susanne Dam (Frontiers in Immunology, 2022)
Introduction Impairment of the innate immune function may contribute to the increased risk of bacterial and viral infections in people with HIV (PWH). In this study we aimed to investigate the induced innate immune responses in PWH prior to and after initiation of combinational antiretroviral therapy (cART). Furthermore, we aimed to investigate if the induced innate immune responses before initiation of cART were associated with CD4+ T-cell recovery one year after initiating cART. Material and method The induced innate immune response was assessed by the TruCulture® whole blood technique in 32 PWH before cART initiation and after 1, 6 and 12 months. To mimic bacterial and viral infections we used a panel of three stimuli (lipopolysaccharide (LPS), resiquimod (R848), and polyinosinic:polycytidylic acid (Poly I:C)) to stimulate the extracellular Toll-like receptor (TLR) 4 and the intracellular TLR7/8 and TLR3, respectively. The following cytokine responses were analyzed by Luminex 200: Tumor Necrosis Factor (TNF)-α, Interleukin (IL)-1b, IL-6, IL-8, IL-10, IL-12p40, IL17A, Interferon (IFN)-α, and IFN-γ. Results At baseline PWH with nadir CD4+ T-cell count <350 cell/µL had lower levels of LPS-, R848-, and Poly I:C-induced IL-6 and IFN-γ, LPS- and R848-induced TNF-α and IL-12, LPS induced IL-1b, and R848-induced IL-10 than PWH with nadir CD4+ T-cell count >350 cells/µL. The majority (>50%) had induced cytokine concentrations below reference levels at baseline which was most pronounced for the LPS- and Poly I:C-induced responses. The induced responses in the whole population improved after 12 months of cART, and more PWH had induced cytokine concentrations within the reference intervals after 12 months. However, the majority of PWH still had LPS-induced INF-α, INF-γ and Poly I:C-induced TNF-α and IL-6 below the reference interval. The induced innate immune responses before cART initiation were not associated with the CD4+ T-cell recovery after 12 months of cART. Conclusion The innate immune response was impaired in PWH, with a more pronounced impairment in PWH with low nadir CD4+ T-cell count. Initiation of cART improved the innate immune response, but compared to the reference intervals, some impairment remained in PWH without viral replication.